Patient specific approach to analysis of shear-induced platelet activation in haemodialysis arteriovenous fistula - Salikhova, Tatiana Yu; Pushin, Denis M.; Nesterenko, Igor V.; Biryukova, Lyudmila S.; Guria, Georgy Th (PLOS ONE, 2022)
Shear-induced platelet activation (SIPAct) is an important mechanism of thrombosis initiation under high blood flow. This mechanism relies on the interaction of platelets with the von Willebrand factor (VWF) capable of unfolding under high shear stress. High shear stress occurs in the arteriovenous fistula (AVF) commonly used for haemodialysis. A novel patient-specific approach for the modelling of SIPAct in the AVF was proposed. This enabled us to estimate the SIPAct level via computational fluid dynamics. The suggested approach was applied for the SIPAct analysis in AVF geometries reconstructed from medical images. The approach facilitates the determination of the SIPAct level dependence on both biomechanical (AVF flow rate) and biochemical factors (VWF multimer size). It was found that the dependence of the SIPAct level on the AVF flow rate can be approximated by a power law. The critical flow rate was a decreasing function of the VWF multimer size. Moreover, the critical AVF flow rate highly depended on patient-specific factors, e.g., the vessel geometry. This indicates that the approach may be adopted to elucidate patient-specific thrombosis risk factors in haemodialysis patients.